2004
DOI: 10.1023/b:mcbi.0000044315.74038.78
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hemodialysis on serum lipids and phospholipids of end-stage renal failure patients

Abstract: Patients with chronic renal failure undergoing periodic maintenance hemodialysis frequently present dyslipoproteinaemia which has been linked to the sharply increased risk of cardiovascular disease in these subjects. Reported defects on lipoprotein-related enzyme activities suggest a possible influence of hemodialysis not just to plasma lipid and lipoprotein levels but also to the composition of cell membranes. In this study, it was investigated whether the reported lipid abnormalities are accompanied by chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
4
15
0
Order By: Relevance
“…In agreement with recent studies [19,20], we found that HDL2 and HDL3-C levels are decreased in the serum of HD patients compared to normal controls. Although HDL metabolism is regulated by several enzymes, such as hepatic triglyceride lipase, cholesterylester transfer protein and LCAT, there is limited evidence in the literature about the involvement of the first two of these in the distribution of HDL2 and HDL3-C subclasses in HD patients [33].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with recent studies [19,20], we found that HDL2 and HDL3-C levels are decreased in the serum of HD patients compared to normal controls. Although HDL metabolism is regulated by several enzymes, such as hepatic triglyceride lipase, cholesterylester transfer protein and LCAT, there is limited evidence in the literature about the involvement of the first two of these in the distribution of HDL2 and HDL3-C subclasses in HD patients [33].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we examined the association of oxLDL with lipids, lipoproteins and apolipoproteins, as well as with CRP in patients with end-stage renal failure on HD. We focused on the association of oxLDL with HDL2 and HDL3-C subclasses, which have differences in their chemical composition and have been proved to be affected by HD [19,20]. This analysis may provide additional information about the effects of oxidative stress on HDL-C activity.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the overall decreased PC observed in this study was apparently not suffi cient to cause major structural changes in the LDL, as there was no signifi cant change in the size of the LDL particles in CKD. The decrease in PCs observed is in agreement with a previous report on levels of PC in plasma of ESRF patients ( 43 ), and also with the observation that PCs are lost in urine of patients with CKD ( 44 ). The lower levels of STs and CSs in LDL of CKD patients are in agreement with some previous studies ( 17 ).…”
Section: Statistical Analysis Discriminated Control and Ckd Ldl Lipidsupporting
confidence: 93%
“…17 However, it contradicts with other studies where decreased levels of the largest HDL2b subclass and increased levels of small HDL3a subclass were separated from plasma of HD patients by polyacrylamide gradient gel electrophoresis 16 or decreased levels of both HDL2-C and HDL3-C were found. 19,20 The above discrepancies could be either the result of different procedures of HDL-C subclass isolation or due to statistical comparison of different number of sample groups. The alteration of HDL-C subclass composition in dialysis patients compared with controls may have clinical relevance in the atherogenesis process in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…14 There is limited evidence concerning the comparison of oxLDL concentration in patients treated with different modes of dialysis, 15 although there are few studies about the comparison of antibodies against oxLDL in dialysis subgroups of patients. Also to our knowledge, the effect of hemodialysis (HD) on distribution of HDL subclasses in serum has been studied recently [16][17][18][19][20] but no data about the effect of peritoneal dialysis (PD) have been reported. This study attempts to look into the comparison of oxLDL levels, lipids, and lipoproteins in patients on HD and PD and in normal controls (NC).…”
Section: Introductionmentioning
confidence: 99%